A genome-wide screen for genes affecting eisosomes reveals Nce102 function in sphingolipid signaling - Fröhlich, Florian (The Rockefeller University Press, 2009)
The protein and lipid composition of eukaryotic plasma membranes is highly dynamic and regulated according to need. The sphingolipid-responsive Pkh kinases are candidates for mediating parts of this regulation, as they affect a diverse set of plasma membrane functions, such as cortical actin patch organization, efficient endocytosis, and eisosome assembly. Eisosomes are large protein complexes underlying the plasma membrane and help to sort a group of membrane proteins into distinct domains. In this study, we identify Nce102 in a genome-wide screen for genes involved in eisosome organization and Pkh kinase signaling. Nce102 accumulates in membrane domains at eisosomes where Pkh kinases also localize. The relative abundance of Nce102 in these domains compared with the rest of the plasma membrane is dynamically regulated by sphingolipids. Furthermore, Nce102 inhibits Pkh kinase signaling and is required for plasma membrane organization. Therefore, Nce102 might act as a sensor of sphingolipids that regulates plasma membrane function.